A Conceptual Framework for Integrating SUS into ITIL: Enhancing IT Service Management Through Usability Evaluation - Rakhmadi, Aris; Rochmadi, Tri; Azis, Abdul; Ayuningtyas, Astika; Sarmini; Wahyusari, Retno (The Indonesian Journal of Computer Science, 2025)
Effective IT service management must combine operational excellence with seamless user experience in today's digital era. This paper introduces the Deployment and Integration Framework for Assessment (DIFA), a conceptual model that integrates the System Usability Scale (SUS) within the IT Infrastructure Library (ITIL) framework. ITIL offers a structured approach to aligning IT services with business objectives, while SUS provides reliable usability measurements from the user's perspective. By embedding SUS assessments throughout ITIL's lifecycle—spanning service strategy, design, transition, operation, and continual improvement—DIFA enables organizations to evaluate and enhance IT services' usability systematically. This integration bridges the gap between process efficiency and user satisfaction, supporting informed decision-making, improved service adoption, and better alignment with user needs. The findings highlight the strategic value of combining usability evaluation with ITIL's best practices, offering a sustainable and scalable pathway for organizations to deliver IT services that are both technically robust and intuitively user-friendly.